Gaps in tipping points research across freshwater, marine, and terrestrial ecosystems - Meagan Harper; Charlotte Carrier-Belleau; Trina Rytwinski; Brian Helmuth; Irena F. Creed; John P. Smol; Joseph R. Bennett; Dalal E.L. Hanna; Leonardo A. Saravia; Juan Rocha; Aubrey Foulk; Sam Dupont; et al. (Biological Conservation, 2026)

Planning sustainable heat networks: governance and sociotechnical practices in Northeast England - William Otchere-Darko; Michael Crilly; Tyne Jenkinson; Caitlin Harper; Emily Ingall-Tombs; Esmee Bryson-Harris; Eleanor Ritchie; Ryan Siu; Sam Wightman; Alexander Kearns (Sustainability Science, 2025)
District heating (DH) forms part of decarbonised energy pathways, potentially offering decentralised, cheap heating for dense urban areas. Entailing both carbonised and decarbonised heat sources, with multiple and overlapping technologies, DH is situated within the milieu of energy and urban planning. This presents questions as to how local governance arrangements and practices are created/emerge to respond to/(co)produce its spatial, energy and technological materialisations. Utilising mixed methods, the study focuses on selected DH projects in Northeast England—a region with historic coal infrastructure and recent heat network projects. Findings first show forms of partnership, outsourcing and subsidiarising as governance arrangements surrounding the DH projects in sharing expertise, resources and risks. These arrangements are implemented through legal agreements, negotiations, reporting mechanisms as well as infrastructure and heat co-production practices. Secondly, these diverse governance arrangements also reflect attempts to address funding, energy security and regulatory issues increasingly refracted through local geothermal endowments and incumbent gas incentives. In effect, the research notes that policy and governance practices should be responsive to a heterogeneous, hybrid and co-produced heatscape, challenging the ideal of transitioning to a uniform DH.

Investigating indoor VOC complexities in rural Beijing: Environmental, resident behavioral, and household energy-use paradigms - Jian Ma; Xiaojing Zhu; Xiaoying Li; Xiang Zhang; Fangxin Zhao; Anqi Zhao; Kaibing Xue; Qinping Song; Lijing Wang; Xin Zhang; Ellison Carter; Sam Harper; et al. (Building and Environment, 2025)

Moving to a new normal: Analysis of shifting climate normals in New Zealand - Raghav Srinivasan; Trevor Carey‐Smith; Linda Wang; Andrew Harper; Sam Dean; Gregor Macara; Ruotong Wang; Stephen Stuart (International Journal of Climatology, 2024)
New Zealand's National Institute of Water and Atmospheric Research publishes climate normals for New Zealand that are used for reporting the regional state of the climate, climate extremes and variability. Temperature and precipitation patterns are affected by both anthropogenic climate change and natural climate variability which in turn affect the climatological normal values calculated every decade. This study investigates how New Zealand's normals for temperature and precipitation have shifted over time at the national, regional and seasonal scales from the 1941–1970 period to the 1991–2020 period. Contrary to WMO recommendations, but aligned with many other countries, New Zealand's climate normals have traditionally not undergone homogenisation. The impact of introducing some homogenisation in the latest 1991–2020 normals, in contrast to historical non‐homogenized station normals, has been assessed using a new homogenized “Seventeen‐Station” temperature series from 1941 to 2020. We demonstrate that interpolating sparse non‐homogenized normals spatially to a grid can produce significant erroneous patterns and therefore undermine the accuracy of the conclusions drawn when using such normals. We find that the historical non‐homogenized temperature normals have a consistent negative bias in the long‐term trend at national, regional and seasonal scales. Our analysis of homogeneity tested precipitation showed consistent decreases at a national scale across all normal periods relative to the 1951–1980 precipitation normal. We also highlight how fixed period temperature and precipitation normals do not fully reflect the current state of a climate that is influenced by decadal variability and global warming. To derive normals fit for use in a changing climate it is suggested that automated methods for broad data homogenisation be developed along with alternative methods to derive normals that account for a non‐stationary climate.

The Scent of Individual Foraging Bees - Flore Mas; Rachael Horner; Sam Brierley; Aimee Harper; David Maxwell Suckling (Journal of Chemical Ecology, 2020)

Assessing disparities in colorectal cancer mortality by socioeconomic status using new tools: health disparities calculator and socioeconomic quintiles - Nancy Breen; Denise Riedel Lewis; James Todd Gibson; Mandi Yu; Sam Harper (Cancer Causes & Control, 2017)

Humoral immunity in the Friend retrovirus infection model - Kalani Halemano; Michael S. Harper; Kejun Guo; Sam X. Li; Karl J. Heilman; Bradley S. Barrett; Mario L. Santiago (Immunologic Research, 2013)

Global socioeconomic inequalities in tobacco use: internationally comparable estimates from the World Health Surveys - Sam Harper; Brittany McKinnon (Cancer Causes & Control, 2012)